Improving Pupil Support Delivery in Schools by Promoting Inclusive Education - Vaitkuvienė - Zimina, Žana; Bruzgelevičienė, Ramutė (Pedagogika, 2016)
The article explores the ways to improve the pupil support system in school practice as part of the transition from integration to the inclusive education of pupils with special needs. The research question addresses the ways of improving the pupil support system in a school focused on inclusive education. Determining the ways of improving the pupil support system in school practice by promoting inclusive education following the case study of Verdenė Gymnasium in Visaginas can be described as the subject of the research. The objective of the research is to outline directions for improving the pupil support system in schools while focusing on the targets of inclusive education. The tasks of the research include: 1) analysing theoretical and operational guidelines provided in scientific literature and education guidance documents on the development of the pupil support system in inclusive schools; 2) determining the reasons why the current pupil support system in school needs improvement whenever the focus is placed on inclusive education; 3) drawing up guidelines for schools to help them upgrade the pupil support system based on inclusive education. Case study is used as the method of this research (Yin, 2003) focusing on an educational institution – gymnasium (grammar school). The choice of the case was determined by the distinctive character of the gymnasium: it delivers a broad range of curricula including an accredited secondary education programme (two years), two-part basic education programme (six years), primary education programme (four years) along with adapted and personalized programmes in primary and basic education and social skills development; it also provides the necessary support for pupils with a variety of special educational needs. The applied research methods include the analysis of written documents, a questionnaire survey and modelling. Units of analysis include national and school documents, teachers and other experts related to the case study schools and the research context. The theoretical and empirical study of the case established that: The implementation of the UNESCO proposed inclusive education concept is still a target to be achieved in the case study school. The school focuses on the types of pupil support established nationwide, which exclude children having special educational needs due to their exceptional abilities, nor do they place emphasis on the need for day to day teacher’s help, thus narrowing the scope of inclusive education. Pupil support in the case study school is institutionalised, its provision being entrusted to different bodies and structures. School documents by themselves postulate the philosophy of inclusive education; however, when it comes to education delivery, integration rather than inclusive education of SEN children tends to prevail in the school: pupils with SEN and gifted children are treated as homogeneous groups without highlighting the importance of the teacher’s help for all student groups in daily education process. The case study schools and other context schools delegate responsibility for inclusive education to SEN teachers and for the education of gifted children to other appointed teachers. The analysis of the research data leads to a conclusion that pupil support delivered by the case study schools is now in the phase of the deconstruction of special needs education and the formation of inclusive education; therefore, it needs improvement implementing inclusive education in line with the philosophy of togetherness and appreciation of diversity, which grants equal opportunities and respect for individuality.